Pemanfaatan Sekam Padi menjadi Saver Briquette dalam Mengasah Kemampuan Bisnis dan Kepekaan Mahasiswa terhadap Lingkungan - Firdausy, A'yun Amalia; Harahap, Hesti Mardiana; nugraha, Dhimas Setya; Syafiq, Muhammad; Hidayah, Nila (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
The Food Security and Agriculture Office of Bantul Regency explains that during 2023 the rice harvest area in Bantul will reach 28,500 hectares. In the harvest period from February to April in 2024, the Head of the Food Security and Agriculture Service of Bantul Regency believes that the rice harvest area in Bantul will reach 4,000 hectares with a production of 8.8 tons of milled dry grain per hectare. Based on this data, Bantul is a potential area to support alternative energy contributions by utilizing rice husk waste into safe fuel. The rice husk saver briquette aims to provide a solution to this problem while utilizing the abundant biomass energy opportunities, especially in Bantul Regency, Yogyakarta. Husk saver briquette is an environmentally friendly biomass charcoal that can be used as a natural fuel and aromatherapy for the community. This activity is in the form of team empowerment between students and supervisors. Products produced through innovations made by the team include original rice husk briquettes, aromatherapy briquettes and mixed briquettes packaged with attractive boxes so as to maintain the quality of briquettes to consumers. Marketing is carried out both offline and online and this product has a license in the form of an NIB (Business License Number). Through this empowerment activity, students can hone their business skills and measure their sensitivity.